Preferable timing of intraductal ultrasonography during endoscopic retrograde cholangiopancreatography lithotomy: A prospective cohort study - Lu, Zhanjun; Zhao, Hang (Frontiers in Medicine, 2022)
Abstract AIM Intraductal ultrasonography (IDUS) is a highly sensitive and non-invasive detective method that can be used to detect complete calculus clearance during endoscopic retrograde cholangiopancreatography (ERCP). In this study, we examined the preferable timing of IDUS during ERCP lithotomy. METHODS From 2017 to 2020, patients with choledocholithiasis were randomized into IDUS-BL (IDUS performed before lithotomy) group，IDUS-ALC(cholangiography and IDUS performed after lithotomy) group, and IDUS-AL group (IDUS performed after lithotomy) group . The influence of IDUS on the accuracy of prejudgement, the incidence of residual stones, the need for repeated lithotomy (RL), and fluoroscopy time were analyzed. RESULTS A total of 184 patients were enrolled. No residual stones were found during follow-up in any of the three groups. There was no difference in prejudgment accuracy rate on size and number of stones between different groups (all p>0.05). RL were performed in 5, 9, and 9 cases of IDUS-BL, IDUS-ALC, and IDUS-AL group, respectively (p>0.05). IDUS-AL group had a shorter fluoroscopy time than the other two groups (1.5±0.6 vs. 2.8±1.2, 2.5±1.0 minutes p<0.05). Incidence of RL was related to the location of calculus (middle or lower part of CBD), lithotripsy, dilated CBD (2.12±0.46 vs. 1.78±0.40 cm p<0.01), and inaccuracy prejudgement. CONCLUISION IDUS performed after lithotomy is preferable for shorten fluoroscopy time during ERCP. IDUS is a reliable solution for the stone omission,which may be more valuable for patients with high-risk factors of RL.